Ionization potential and structure relaxation of adenine, thymine, guanine and cytosine bases and their base pairs: a quantification of reactive sites - Mishra, Deepti; Pal, Sourav (Journal of Molecular Structure-Theochem, 2009)
We present density functional theory (DFT) calculations using B3LYP/6-31++G** method to show relaxation in geometry of base pairs on cation radical formation. The changes in hydrogen bond length and angles show that in the cationic radical form the structure of the base pairs relaxes due to the distribution of charge. According to a recent study. it has been found that, upon excitation hole transfer from base to sugar occurs which results in sugar radical formation and leads to strand breakage 145] [A. Kumar, M.D. Sevilla, J. Phys. Chem. B 110 (2006) 24181]. One hydrogen bond increases, while the other decreases in Adenine-Thymine (AT) base pair and in case of Guanine-Cytosine (GC) base pair. one bond increases and other two decrease. Same is the case with bond angles for both the base pairs. Analysis of the electron density map of Singly Occupied Molecular Orbital (SOMO) reveals that electron is transferred mainly from adenine and guanine bases in the cationic radical formation of AT and CC base pair, respectively. The reactive sites of bases have been analyzed using condensed Fukui functions in a relaxed and frozen core approximation. The effects of relaxation on the reactivity indices are also analyzed. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Base-pairs; DNA bases; Fukui function; H-bond length; Ionization potential